Comparative Study of the Phytoprostane and Phytofuran Content of indica and japonica Rice (Oryza sativa L.) Flours - Pinciroli, María (2017)
Phytoprostanes and phytofurans (PhytoPs and PhytoFs, respectively) are nonenzymatic lipid peroxidation products derived from α-linolenic acid (C18:3 n-3), considered biomarkers of oxidative degradation in plant foods. The present work profiled these compounds in white and brown grain flours and rice bran from 14 rice cultivars of the subspecies indica and japonica by ultrahigh performance liquid chromatography coupled to electrospray ionization and triple quadrupole mass spectrometry. For PhytoPs, the average concentrations were higher in rice bran (0.01−9.35 ng g−1) than in white and brown grain flours (0.01−1.17 ng g−1). In addition, the evaluation of rice flours for the occurrence PhytoFs evidenced average values 1.77, 4.22, and 10.30 ng g−1 dw in rice bran, brown grain flour, and white grain flour, respectively. A significant correlation was observed between total and individual compounds. The concentrations retrieved suggest rice bran as a valuable source of PhytoPs and PhytoFs that should be considered in further studies on bioavailability and bioactivity of such compounds.